Floating floor system and method of making

CN121066305BActive Publication Date: 2026-10-27SICHUAN HUANUOBANG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511295622.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-11
Publication Date
2026-10-27
Estimated Expiration
2045-09-11

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供采用一种浮筑楼板隔声系统及其制备方法,以提高拼缝处隔声性能,避免应拼缝处漏声导致的隔声系统隔声效果差的问题

Benefits of technology

1、本发明的锁缝剂采用水泥作为基材,通过添加纳米二氧化硅作为无机填料,能够提高水泥基材固化后的密实度,在一定程度上提高水泥的隔声效果,通过添加丙烯酸橡胶共混乳液,能提高锁缝剂韧性进而提高了抗裂效果;本发明蒙脱石改性聚氨酯作为隔声材料,通过蒙脱石共混改性后,能够大幅度提高聚氨酯的隔声效果,可以有效降低拼缝的漏声率;纳米钛酸盐和硅烷偶联剂协同作用,可提高锁缝剂中各个组份的共混效果,进而提高锁缝剂的隔声效果,进一步降低拼缝的漏声率,即本发明所设计的拼缝剂避免应拼缝处漏声导致的隔声系统隔声效果差的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121066305B_ABST
    Figure CN121066305B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of architectural acoustics engineering, and particularly discloses a floating building floor sound insulation system and a preparation method thereof, which is formed by splicing a plurality of sound insulation mats; a lock joint agent is poured at a splicing joint, and the lock joint agent comprises the following components in parts by weight: 10-15 parts of acrylic rubber blended emulsion, 30-40 parts of nano silicon dioxide, 40-60 parts of sulphoaluminate cement, 5-8 parts of nano titanate, 15-20 parts of silane coupling agent and 10-25 parts of montmorillonite modified polyurethane; wherein the acrylic rubber blended emulsion is prepared by mixing rubber particles into an aqueous solution prepared from acrylic latex powder; and the montmorillonite modified polyurethane is prepared by using a melt blending method. The sound insulation performance at the splicing joint is improved, and the problem of poor sound insulation effect of the sound insulation system caused by sound leakage at the splicing joint is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of architectural acoustics engineering technology, specifically to a floating floor sound insulation system and its preparation method. Background Technology

[0002] In the field of sound insulation for building floors, especially for the isolation of impact noise, floating floor construction is a widely adopted and effective solution. Its core principle is to place an elastic sound-insulating layer between the structural floor slab and the finishing layer, thus cutting off the sound bridge transmission path.

[0003] Currently, sound insulation layers used for floating floors include polyethylene rubber pads, rock wool boards, and foamed boards made of plastics. For example, CN104120814B discloses a sound insulation floor slab with micro-foamed board as the sound insulation pad and its construction method. It uses micro-foamed boards made of plastics such as polyvinyl chloride, polyethylene, polypropylene, polystyrene, ABS, polymethyl methacrylate, phenolic resin, and urea-formaldehyde resin. This micro-foamed board sound insulation pad material has good comprehensive performance in terms of sound insulation, compression resistance, water absorption, mildew resistance, and creep resistance. It can reduce the impact sound pressure intensity of the floor slab by about 8-20 dB. At the same time, a 20-40 mm cement mortar protective layer and surface material can be directly laid on it, thus solving the problems of excessive reduction in net height and excessive increase in load caused by the reinforced concrete protective layer in traditional floating floors.

[0004] Although the micro-foamed board prepared by CN104120814B can effectively reduce the sound pressure intensity of impact sound, in actual construction, when the micro-foamed board is used for floating floor slabs, it is not a complete one-piece molded board, but needs to be spliced ​​together from multiple micro-foamed boards. If the joints are not properly treated, sound leakage at the joints will occur. There is little attention paid to the problem of sound leakage at the joints in the existing technology, and the crack resistance and compressive strength of the micro-foamed board prepared by CN104120814B also need to be improved. Summary of the Invention

[0005] The purpose of this invention is to provide a floating floor slab sound insulation system and its preparation method to improve the sound insulation performance at the joints and avoid the problem of poor sound insulation effect caused by sound leakage at the joints.

[0006] This invention is achieved through the following technical solution: A floating floor sound insulation system is composed of several sound insulation pads spliced ​​together; a joint sealant is injected at the joints, the joint sealant comprising the following components by weight: 10-15 parts of acrylic rubber blend emulsion, 30-40 parts of nano silica, 40-60 parts of sulfoaluminate cement, 5-8 parts of nano titanate, 15-20 parts of silane coupling agent, and 10-25 parts of montmorillonite modified polyurethane. Among them, the acrylic rubber blend emulsion is made by mixing rubber particles with an aqueous solution prepared from acrylic latex powder; Montmorillonite-modified polyurethane is prepared by melt blending montmorillonite and polyurethane particles.

[0007] The acrylic latex powder of the present invention is prior art; it is prepared using existing methods, specifically including the following steps: A: Mix 20-30 parts by weight of acrylic monomer, 40-50 parts by weight of acrylate monomer and 5-10 parts by weight of N-vinylpyrrolidone, heat to 50-60°C, add 2-5 parts by weight of emulsifier and 20-30 parts by weight of water to obtain emulsion. B: According to the weight, add 5-10 parts of the first initiator solution dropwise to the emulsion, heat to 70-80℃, keep the temperature for 1-2 hours, then add 10-20 parts of acrylic acid and 25-35 parts of trimethylolpropane, cool to 56-60℃, and react for 1-1.5 hours to obtain the initial product. C: Dissolve 20-25 parts of sodium silicate in water by weight, add the initial product while stirring at 90-100℃, stir until the water evaporates, pulverize, and obtain acrylic latex powder.

[0008] The sealant of this invention is based on the practical application scenario of floating floor slabs, using cement as the base material. The sulfoaluminate cement used in this invention has superior resistance to sulfate corrosion, high temperature resistance, and adaptability to extreme environments compared to ordinary silicate cement. By adding nano-silica as an inorganic filler, the density of the cement base material after curing can be improved, thereby improving the sound insulation effect of the cement to a certain extent. By adding acrylic rubber blend emulsion, not only can the adhesion performance of the prepared sealant be improved, but its toughness can also be improved, thus improving the crack resistance. Specifically, an acrylic emulsion is formed by mixing acrylic latex powder in an aqueous solution. The acrylic emulsion not only has good adhesion performance, but also provides an aqueous solution for configuring the various components into a slurry. Then, the acrylic emulsion rubber is added, as rubber has a toughening effect.

[0009] Polyurethane is a common sound insulation material, but its sound insulation effect is limited and it is not well applied to floating floors because the sound insulation of floating floors needs to take impact sound into account.

[0010] This invention uses montmorillonite-modified polyurethane as a sound insulation material. After montmorillonite blending and modification, the sound insulation effect of polyurethane can be greatly improved, and the sound leakage rate of the joints can be effectively reduced.

[0011] The synergistic effect of the nano-titanium salt and silane coupling agent of the present invention can improve the blending effect of each component in the lock sealant, thereby improving the sound insulation effect of the lock sealant and further reducing the sound leakage rate of the joint.

[0012] In summary, the joint sealant involved in this invention can improve the sound insulation performance at the joints and avoid the problem of poor sound insulation effect of the sound insulation system caused by sound leakage at the joints.

[0013] The addition of montmorillonite can improve the sound insulation performance of polyurethane within a certain range. However, when the amount of montmorillonite is increased to a certain extent, it will actually reduce the improvement of sound insulation performance. This is because adding too much montmorillonite will cause agglomeration, which is not conducive to improving sound insulation performance.

[0014] Therefore, when montmorillonite is added to a certain amount, it is no longer possible to improve the sound insulation performance of polyurethane by adding montmorillonite. If only montmorillonite is used to improve the sound insulation performance of polyurethane, in a preferred method, the amount of montmorillonite is 2.0-2.5% by weight of polyurethane particles.

[0015] In a preferred embodiment, carbon black and polyethyleneimine are added to the montmorillonite-modified polyurethane.

[0016] Carbon black and polyethyleneimine can further improve the sound insulation effect of montmorillonite-modified polyurethane to a certain extent. Carbon black itself has a certain sound insulation effect and can also improve the flowability of materials, while polyethyleneimine can improve the dispersion effect of montmorillonite in polyurethane.

[0017] Therefore, by simultaneously adding carbon black and polyethyleneimine to montmorillonite-modified polyurethane, the sound insulation effect of montmorillonite-modified polyurethane can be improved.

[0018] In a preferred embodiment, since carbon black itself has a certain sound insulation effect, the amount of carbon black used is higher than the amount of polyethyleneimine used; specifically, the mass ratio of polyethyleneimine to montmorillonite is (0.5-0.8):(0.2-0.3):1.

[0019] In a preferred embodiment, since the simultaneous addition of carbon black and polyethyleneimine can improve the dispersibility of montmorillonite in polyurethane, the amount of montmorillonite can be appropriately increased to improve the sound insulation effect of polyurethane. Specifically, in montmorillonite-modified polyurethane prepared with the addition of carbon black and polyethyleneimine, the amount of montmorillonite can be increased to 2.0-5.0% by weight of polyurethane particles, preferably 4.0-5.0%.

[0020] In a preferred embodiment, the nano titanate includes at least one of nano barium titanate, nano strontium titanate, nano calcium titanate, nano potassium titanate, and nano sodium titanate.

[0021] In a preferred embodiment, the silane coupling agent is a liquid silane coupling agent, comprising at least one of γ-aminopropyltriethoxysilane, 3-aminopropyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.

[0022] Liquid silane coupling agents can fulfill their basic functions and provide an aqueous environment for the mixing of various components in lock sealant.

[0023] In a preferred embodiment, the sound insulation pad consists of a non-woven composite layer, an elastic support layer, and a sound insulation and vibration damping layer, arranged from bottom to top.

[0024] The main function of the sound insulation and vibration damping layer is sound insulation, the main function of the elastic support layer is buffering, and the function of the non-woven composite layer is to improve the crack resistance of the sound insulation pad. The sound insulation and vibration damping layer can be made of any existing material with sound insulation effect, and the elastic support layer can be made of any existing material with good compressive strength and a certain degree of toughness.

[0025] In a preferred embodiment, the sound insulation and vibration damping layer comprises an acrylic rubber blend emulsion and butyl rubber / asphalt composite damping particles, with the butyl rubber / asphalt composite damping particles accounting for 35-45% by weight of the acrylic rubber blend emulsion. The elastic support layer comprises an acrylic rubber blend emulsion, quartz sand, and a halogen-free flame retardant, with the quartz sand accounting for 40-50% and the halogen-free flame retardant accounting for 20-25% by weight of the acrylic rubber blend emulsion. The halogen-free flame retardant specifically includes magnesium hydroxide, aluminum hydroxide, and organophosphates, etc.

[0026] In a preferred embodiment, the particle size of the butyl rubber / asphalt composite damping particles is 50-150 μm; the quartz sand is sieved through a 40-70 mesh screen.

[0027] Specifically, the butyl rubber / asphalt composite damping particles are made by mixing butyl rubber particles with a particle size of 50-150μm and asphalt particles with a particle size of 50-150μm at a mass ratio of 2:1.

[0028] In a preferred embodiment, the nonwoven composite layer is formed by hot-melt penetration of a crack-resistant composite material into a polyester nonwoven fabric; the crack-resistant composite material includes expanded perlite and polypropylene fibers, with a mass ratio of expanded perlite to polypropylene fibers of 1:(2-4).

[0029] The polypropylene fiber used is short fiber, 5-10mm in length, and has crack resistance. Expanded perlite has a certain sound absorption capacity and high compressive strength. The nonwoven composite layer, infused with expanded perlite and polypropylene fiber through a melt-permeation process, not only has excellent crack resistance but also excellent compressive strength and a certain degree of sound insulation and energy absorption. It is particularly suitable for sound insulation pads in floating floors. Since the sound insulation pads in floating floors are placed between the structural floor slab and the finishing layer, they need to be subjected to a certain amount of pressure during use. Therefore, the nonwoven composite layer, which combines crack resistance and compressive strength, is particularly suitable for this application.

[0030] In a preferred embodiment, the crack-resistant composite material contains nano-silica and a plasticizer, wherein the amount of nano-silica is 20-30% and the amount of plasticizer is 8-10% by weight of expanded perlite.

[0031] Among them, nano-silica can improve the strength of polypropylene fibers, improve their mechanical properties and thus improve crack resistance; plasticizers can lower the glass transition temperature of polypropylene fibers, so that they can still maintain good toughness at low temperatures; plasticizers can specifically be di-n-butyl phthalate (DBP), diisobutyl phthalate (DIBP), butyl benzyl phthalate (BBP), di(2-ethylhexyl) phthalate (DEHP), etc.

[0032] Although the addition of nano-silica can improve the strength of the nonwoven composite layer, adding too much nano-silica can affect the tensile properties. Therefore, it is necessary to reasonably control the amount of nano-silica used. This invention uses the synergistic effect of nano-silica and plasticizer to improve the strength and toughness of polypropylene fibers, thereby improving the crack resistance of the nonwoven composite layer.

[0033] The thicknesses of the non-woven composite layer, the elastic support layer, and the sound insulation and vibration damping layer are 1-2mm, 1-2mm, and 3-5mm, respectively.

[0034] The seam between two adjacent sound insulation pads is a T-shaped seam.

[0035] A method for preparing a floating floor sound insulation system includes the following steps: S1. Prepare the non-woven composite layer, elastic support layer and sound insulation and vibration damping layer respectively; S2. The non-woven composite layer, elastic support layer and sound insulation and vibration damping layer are combined to form a sound insulation pad, and splicing ends are formed in the sound insulation pad; S3. Join several sound insulation pads together using the splicing ends, and then inject a sealing agent into the joint at 0.3-0.5MPa.

[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The joint sealant of this invention uses cement as a base material. By adding nano-silica as an inorganic filler, the density of the cement base material after curing can be improved, thereby improving the sound insulation effect of the cement to a certain extent. By adding acrylic rubber blend emulsion, the toughness of the joint sealant can be improved, thus improving the crack resistance. The montmorillonite-modified polyurethane of this invention is used as a sound insulation material. After montmorillonite blending modification, the sound insulation effect of polyurethane can be significantly improved, which can effectively reduce the sound leakage rate of the joint. The synergistic effect of nano-titanium and silane coupling agent can improve the blending effect of each component in the joint sealant, thereby improving the sound insulation effect of the joint sealant and further reducing the sound leakage rate of the joint. That is, the joint sealant designed by this invention avoids the problem of poor sound insulation effect of the sound insulation system caused by sound leakage at the joint.

[0037] 2. This invention designs the sound insulation pad as consisting of a non-woven fabric composite layer, an elastic support layer, and a sound insulation and vibration damping layer, arranged from bottom to top. The main function of the sound insulation and vibration damping layer is sound insulation; the main function of the elastic support layer is buffering; and the function of the non-woven fabric composite layer is to improve the crack resistance of the sound insulation pad. By combining the non-woven fabric composite layer, the elastic support layer, and the sound insulation and vibration damping layer to create a sound insulation pad, it not only has sound insulation properties but also excellent crack resistance, making it particularly suitable for floating floor slabs.

[0038] 3. The nonwoven composite layer of the present invention is formed by hot-melt penetration of crack-resistant composite material into polyester nonwoven fabric; the crack-resistant composite material includes expanded perlite and polypropylene fiber. The added expanded perlite and polypropylene fiber can improve the compressive and tensile strength of polyurethane nonwoven fabric, thereby improving the crack resistance of polyurethane nonwoven fabric; by adding nano silica and plasticizer, the crack resistance of polyurethane nonwoven fabric can be further improved.

[0039] 4. The seam of the present invention is a T-shaped groove. When used with the sealing agent of the present invention, it can effectively reduce the sound leakage rate at the seam of the sound insulation pad. Attached Figure Description

[0040] The accompanying drawings, which are included to provide a further understanding of embodiments of the invention and form part of this application, do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the structure of the sound insulation pad of the present invention; Figure 2 This is a side view of the T-shaped groove of the present invention; Figure 3 This is a top view of the T-shaped groove of the present invention; Figure 4 This is a photograph of the nonwoven composite layer prepared in Example 4 of the present invention. Figure 5 This is a photograph of the actual product after the sealant has been applied to a flat surface and dried, as shown in Embodiment 3 of the present invention. Figure 6This image shows the slurry state of the sealant formulation described in Example 3 of the present invention, as prepared during the construction process.

[0041] The attached diagram shows the markings and corresponding component names: 1-Non-woven composite layer; 2-Elastic support layer; 3-Sound insulation and vibration damping layer; 100-Sound insulation pad; 101-T-shaped groove. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The illustrative embodiments and descriptions of this invention are for illustrative purposes only and are not intended to limit the invention. The embodiments described below are some, but not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0043] In the following description, numerous specific details are set forth to provide a thorough understanding of the invention. However, it will be apparent to those skilled in the art that these specific details are not necessary to practice the invention. In other embodiments, well-known structures, materials, or methods are not specifically described to avoid obscuring the invention. Unless otherwise specified, the materials, instruments, and reagents used in the following embodiments are commercially available. Unless otherwise specified, the techniques used in the embodiments are conventional methods well known to those skilled in the art.

[0044] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0045] Example: To address the sound leakage problem at the joints of the sound insulation layer in floating floor slabs, this embodiment provides a floating floor slab sound insulation system, which is composed of several sound insulation pads 100 spliced ​​together; a joint sealant is injected at the joints, and the joint sealant comprises the following components by weight: 10-15 parts of acrylic rubber blend emulsion, 30-40 parts of nano silica, 40-60 parts of sulfoaluminate cement, 5-8 parts of nano titanate, 15-20 parts of silane coupling agent, and 10-25 parts of montmorillonite modified polyurethane. The acrylic rubber blend emulsion is prepared by mixing rubber particles with an aqueous solution made from acrylic latex powder. The acrylic latex powder is a prior art product, and its preparation process includes the following steps: A: Mix 20 kg of acrylic monomer, 40 kg of acrylate monomer (20 kg of dicyclopentenyl acrylate and 20 kg of isoborneol acrylate), and 5 kg of N-vinylpyrrolidone, heat to 50°C, and add 2 kg of emulsifier (polyoxyethylene ether, density 1.00 g / cm³). 3 Melting point 41℃, molecular formula C 56 H 114 O 21 Mix 20 kg of water to obtain an emulsion; B: Add 5 kg of the first initiator solution dropwise to the emulsion, heat to 70°C, keep the temperature for 1 hour, then add 10 kg of acrylic acid and 25 kg of trimethylolpropane, cool to 56°C, and react for 1 hour to obtain the initial product. C: Dissolve 20 kg of sodium silicate in water by weight, add the initial product while stirring at 90°C, stir until the water evaporates, pulverize, and obtain acrylic latex powder.

[0046] The first initiator solution was prepared by potassium persulfate and water in a weight ratio of 2:10.

[0047] The preparation process of acrylic rubber blend emulsion is as follows: Mix 6 kg of acrylic latex powder and 55 kg of water until the acrylic latex powder dissolves, then add 35 kg of rubber granules and mix to prepare an acrylic rubber blend emulsion.

[0048] Montmorillonite-modified polyurethane is prepared by melt blending montmorillonite and polyurethane particles. The specific preparation process of montmorillonite-modified polyurethane is as follows: Montmorillonite and polyurethane particles (LC5.0 polyurethane foam particles) were first mixed in a high-speed mixer and then intensively mixed in a torque rheometer at a temperature of 230°C, a speed of 80 r / min, and a time of 8 min. The blend was then extruded and pulverized to obtain powdered montmorillonite-modified polyurethane.

[0049] Among them, nano titanates include at least one of nano barium titanate, nano strontium titanate, nano calcium titanate, nano potassium titanate, and nano sodium titanate.

[0050] The silane coupling agent is a liquid silane coupling agent, including at least one of γ-aminopropyltriethoxysilane, 3-aminopropyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.

[0051] In this embodiment, the joint sealant uses cement as a base material. By adding nano-silica as an inorganic filler, the density of the cement base material after curing can be improved, which to a certain extent improves the sound insulation effect of the cement. By adding acrylic rubber blend emulsion, the toughness of the joint sealant can be improved, thereby improving the crack resistance. Montmorillonite-modified polyurethane is used as a sound insulation material, which can effectively reduce the sound leakage rate of the joint. The synergistic effect of nano-titanium and silane coupling agent can improve the blending effect of each component in the joint sealant, thereby further improving the sound insulation effect of the joint sealant and further reducing the sound leakage rate of the joint.

[0052] The addition of montmorillonite can improve the sound insulation effect of polyurethane within a certain range. However, once the addition reaches a certain level, further increasing the montmorillonite content will not only fail to further improve the sound insulation effect of polyurethane, but will also have the opposite effect. Therefore, it is necessary to reasonably control the amount of montmorillonite. Preferably, the amount of montmorillonite is 2-2.5% based on the weight of polyurethane particles.

[0053] When adding more montmorillonite can no longer further improve the sound insulation effect of polyurethane, it is proposed to consider adding other substances to promote the modification effect of montmorillonite. This embodiment found through experiments that the simultaneous addition of carbon black and polyethyleneimine (CAS9002-98-6) can improve the sound insulation effect of polyurethane. On the one hand, a certain amount of montmorillonite can be added to further improve the sound insulation effect of polyurethane; on the other hand, carbon black itself can be used to improve the sound insulation effect.

[0054] Preferably, the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.5-0.8:0.2-0.3:1.

[0055] Preferably, in the montmorillonite-modified polyurethane prepared with the addition of carbon black and polyethyleneimine, the amount of montmorillonite is 2.0-5.0% by weight of the polyurethane particles, more preferably 4.0-5.0%.

[0056] Preferably, such as Figure 1 As shown, the sound insulation pad 100 consists of a non-woven composite layer 1, an elastic support layer 2, and a sound insulation and vibration damping layer 3 from bottom to top. The elastic support layer 2 and the sound insulation and vibration damping layer 3 can be any existing technology. The thicknesses of the non-woven composite layer 1, the elastic support layer 2, and the sound insulation and vibration damping layer 3 are 1-2 mm, 1-2 mm, and 3-5 mm, respectively.

[0057] Specifically, in this embodiment, the sound insulation and vibration damping layer 3 is composed of an acrylic rubber blend emulsion and butyl rubber / asphalt composite damping particles. The amount of butyl rubber / asphalt composite damping particles is 35-45% by weight of the acrylic rubber blend emulsion. In a specific case, the amount of butyl rubber / asphalt composite damping particles is 40% by weight of the acrylic rubber blend emulsion. The butyl rubber / asphalt composite damping particles are formed by mixing butyl rubber particles with a particle size of 80-100μm and asphalt particles with a particle size of 80-100μm at a mass ratio of 2:1.

[0058] Specifically, in this embodiment, the elastic support layer 2 is composed of an acrylic rubber blend emulsion, quartz sand, and a halogen-free flame retardant. Based on the weight of the acrylic rubber blend emulsion, the amount of quartz sand is 40-50%, and the amount of the halogen-free flame retardant is 20-25%. In a specific case, based on the weight of the acrylic rubber blend emulsion, the amount of quartz sand is 45%, and the amount of the halogen-free flame retardant magnesium hydroxide is 25%; the quartz sand is sieved through a 40-70 mesh screen.

[0059] The acrylic rubber blend emulsion used in the elastic support layer 2 and the sound insulation and vibration damping layer 3 is the same as that used in the lock sealant.

[0060] In this embodiment, the nonwoven composite layer 1 is formed by hot-melt penetration of an anti-cracking composite material into the polyester nonwoven fabric, with a penetration depth > 50 μm. The following specific examples are designed based on a depth of 60 μm. The polyester nonwoven fabric used has a basis weight of 200 g / m² and a thickness of approximately 0.35 mm. The anti-cracking composite material includes expanded perlite and polypropylene fibers, with a mass ratio of expanded perlite to polypropylene fibers of 1:2-4. The polypropylene fibers are short fibers with a length of 5-10 mm. This embodiment utilizes expanded perlite and polypropylene fibers to improve the crack resistance of the nonwoven composite layer 1.

[0061] Preferably, the crack-resistant composite material contains nano-silica and a plasticizer. Based on the weight of expanded perlite, the amount of nano-silica is 20-30%, and the amount of plasticizer is 8-10%. Specifically, the plasticizer can be di-n-butyl phthalate (DBP), diisobutyl phthalate (DIBP), butyl benzyl phthalate (BBP), di(2-ethylhexyl) phthalate (DEHP), etc. Nano-silica and the plasticizer can further improve the crack resistance of the nonwoven composite layer 1.

[0062] like Figure 2 As shown, the seam after splicing two adjacent sound insulation pads 100 is a T-shaped seam.

[0063] The method for preparing the floating floor sound insulation system in this embodiment includes the following steps: S1. Prepare non-woven composite layer 1, elastic support layer 2 and sound insulation and vibration damping layer 3 respectively; The preparation process of the nonwoven composite layer 1 is as follows: After laying the polyurethane nonwoven fabric flat, a layer of crack-resistant composite material is laid on the polyurethane nonwoven fabric, and then the crack-resistant composite material is melt-permeated into the polyester nonwoven fabric under 120℃ / 0.8MPa roller pressing.

[0064] The preparation process of the elastic support layer 2 and the sound insulation and vibration damping layer 3 is as follows: after mixing the various materials in proportion, they are prepared into sheets by extrusion molding process, with an extrusion head temperature of 110℃.

[0065] S2. The non-woven composite layer 1, the elastic support layer 2 and the sound insulation and vibration damping layer 3 are composited by synchronous hot pressing to form a sound insulation pad 100, and a splicing end is formed on the sound insulation pad 100. S3. Several sound insulation pads 100 are spliced ​​together using the splicing ends to form a T-shaped groove 101. Then, a locking agent is injected into the T-shaped groove 101 at a pressure of 0.3-0.5 MPa. The T-shaped groove 101 is as follows: Figure 2 , Figure 3 As shown.

[0066] In this embodiment, the sound insulation pad is designed with, from bottom to top, a non-woven composite layer 1, an elastic support layer 2, and a sound insulation and vibration damping layer 3. The main function of the sound insulation and vibration damping layer 3 is sound insulation; the main function of the elastic support layer 2 is buffering; and the function of the non-woven composite layer 1 is to improve the crack resistance of the sound insulation pad. By combining the non-woven composite layer 1, the elastic support layer 2, and the sound insulation and vibration damping layer 3 to form the sound insulation pad 100, it not only has sound insulation effects but also excellent crack resistance, making it particularly suitable for floating floor slabs.

[0067] To achieve better installation results for the floating floor sound insulation system and avoid gaps in the installation, an adhesive layer is first applied to the structural floor slab before installing the system. Then, a 100mm sound insulation pad is laid, followed by the injection of shrink-fit sealant at the joints. After the sealant has cured, the upper decorative layer is installed. The adhesive formulation consists of 100 parts acrylic emulsion, 15 parts hydrogenated rosin resin, and 30 parts reinforcing filler. The reinforcing filler can be inorganic reinforcing particles such as silica. The adhesive's bonding strength is >1.0 MPa.

[0068] The substances used in this embodiment are all existing and can be obtained through conventional means, such as purchasing.

[0069] To better illustrate the technical effects of this embodiment, the following specific examples are used for explanation: Example 1: A sound insulation pad comprises, from bottom to top, a non-woven composite layer 1, an elastic support layer 2, and a sound insulation and vibration damping layer 3, with thicknesses of 1mm, 1mm, and 4mm respectively; the non-woven composite layer 1, the elastic support layer 2, and the sound insulation and vibration damping layer 3 are composited by synchronous hot pressing to form a sound insulation pad 100.

[0070] Among them, the sound insulation and vibration damping layer 3 is composed of acrylic rubber blend emulsion and butyl rubber / asphalt composite damping particles; the amount of butyl rubber / asphalt composite damping particles is 40% by weight of acrylic rubber blend emulsion; the butyl rubber / asphalt composite damping particles are made by mixing butyl rubber particles with a particle size of 80-100μm and asphalt particles with a particle size of 80-100μm at a mass ratio of 2:1.

[0071] The elastic support layer 2 is composed of acrylic rubber blend emulsion, quartz sand and halogen-free flame retardant magnesium hydroxide. The amount of quartz sand is 45% and the amount of halogen-free flame retardant magnesium hydroxide is 25% based on the weight of the acrylic rubber blend emulsion. The quartz sand is sieved through a 40-70 mesh screen.

[0072] The preparation process of the acrylic rubber blend emulsion used in the elastic support layer 2 and the sound insulation and vibration damping layer 3 is described in the above embodiments.

[0073] In this embodiment, the nonwoven composite layer 1 is formed by hot-melt penetration of a crack-resistant composite material into a polyester nonwoven fabric; the crack-resistant composite material is composed of expanded perlite and polypropylene fibers, with a mass ratio of expanded perlite to polypropylene fibers of 1:3; the polypropylene fibers are short fibers with a length of 5-10 mm. The preparation process of the nonwoven composite layer 1 is described in the above embodiment. The nonwoven composite layer 1 prepared in this embodiment is as follows... Figure 4 As shown.

[0074] Example 2: This embodiment is based on Embodiment 1. The difference between Embodiment 1 and Embodiment 1 is that the crack-resistant composite material used to prepare the nonwoven composite layer 1 is different. The crack-resistant composite material in this embodiment contains nano-silica and plasticizer di-n-butyl phthalate. Based on the weight of expanded perlite, the amount of nano-silica is 25% and the amount of plasticizer is 10%.

[0075] Comparative Example 1: A polyester nonwoven fabric with a basis weight of 200 g / m².

[0076] Comparative Example 2: A nonwoven composite layer, which is the nonwoven composite layer prepared in Example 1.

[0077] Comparative Example 3: A nonwoven composite layer, which is the nonwoven composite layer prepared in Example 2.

[0078] Comparative Example 4: This comparative example is based on Comparative Example 3, but differs from Comparative Example 3 in that: The amount of nano-silica used was increased to 38%.

[0079] Comparative Example 5: This comparative example is based on Comparative Example 3, but differs from Comparative Example 3 in that: The crack-resistant composite material in this comparative example contains only nano-silica and no plasticizer di-n-butyl phthalate.

[0080] Comparative Example 6: This comparative example is based on Example 1, and differs from Example 1 in that: A sound insulation pad, from bottom to top, consists of an elastic support layer 2 and a sound insulation and vibration damping layer 3, i.e., without the non-woven composite layer 1.

[0081] Products prepared according to Examples 1, 2, and Comparative Examples 1-4 were tested for tensile strength and tear strength according to GB / T3923.1-2013 Textiles - Tensile Properties Test. The results are shown in Table 1. Table 1 As can be seen from the data in Table 1: 1) By melt-permeating expanded perlite and polypropylene fibers onto polyester nonwoven fabric, the crack resistance of polyester nonwoven fabric can be improved. Adding nano silica and plasticizer di-n-butyl phthalate to the melt-permeating system can further improve the crack resistance of polyester nonwoven fabric. 2) Adding nano-silica alone has almost no effect on improving the crack resistance of polyester nonwoven fabrics. It requires the synergistic effect of nano-silica and plasticizers. When nano-silica and the plasticizer di-n-butyl phthalate are used simultaneously, excessive nano-silica will significantly reduce the crack resistance of the nonwoven composite layer. 3) By simultaneously hot-pressing a non-woven composite layer 1 onto the bottom of the substrate, which consists of an elastic support layer 2 and a sound insulation and damping layer 3, the crack resistance of the substrate can be greatly improved.

[0082] Therefore, the nonwoven composite layer 1 prepared in Examples 1 and 2 has excellent crack resistance.

[0083] Example 3: A floating floor sound insulation system is composed of several sound insulation pads 100 spliced ​​together. The sound insulation pads 100 are the sound insulation pads prepared in Example 1, and the splice joints are T-shaped grooves 101, as shown in the figure. Figure 2 , Figure 3 As shown; inject sealant into the seams. The sealant consists of the following components by weight: 10 parts acrylic rubber blend emulsion, 40 parts nano silica, 60 parts sulfoaluminate cement, 8 parts nano titanate, 20 parts silane coupling agent, and 25 parts montmorillonite modified polyurethane.

[0084] The preparation process of the acrylic rubber blend emulsion is described in the above examples.

[0085] Montmorillonite-modified polyurethane is prepared by melt blending montmorillonite and polyurethane particles; the preparation process is described in the examples above. During the modification process, the amount of montmorillonite used is 2.0% based on the weight of the polyurethane particles.

[0086] Among them, the nano titanate is nano barium titanate; and the silane coupling agent is liquid silane coupling agent γ-aminopropyltriethoxysilane.

[0087] The actual image of the lock sealant applied and dried on a flat surface in this embodiment is shown below. Figure 5 As shown in the image; the slurry state of the sealant prepared during construction is shown in the image. Figure 6 As shown.

[0088] Example 4: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that the proportions of the various components in the sealant are different, as shown below: A floating floor sound insulation system is composed of several sound insulation pads 100 spliced ​​together, with T-shaped grooves 101 at the joints; a locking agent is injected into the joints, and the locking agent consists of the following components by weight: 15 parts acrylic rubber blend emulsion, 30 parts nano silica, 40 parts sulfoaluminate cement, 5 parts nano titanate, 15 parts silane coupling agent, and 10 parts montmorillonite modified polyurethane.

[0089] Example 5: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: in the preparation process of montmorillonite-modified polyurethane, the amount of montmorillonite used is 2.5% based on the weight of the polyurethane particles.

[0090] Comparative Example 7: This comparative example is based on Example 3, but differs from Example 3 in that the amount of montmorillonite used in the preparation of montmorillonite-modified polyurethane is 1.5% based on the weight of the polyurethane particles.

[0091] Comparative Example 8: This comparative example is based on Example 3, but differs from Example 3 in that: in the preparation of montmorillonite-modified polyurethane, the amount of montmorillonite used is 1.0% based on the weight of the polyurethane particles.

[0092] Comparative Example 9: This comparative example is based on Example 3, but differs from Example 3 in that the amount of montmorillonite used in the preparation of montmorillonite-modified polyurethane is 3.0% based on the weight of the polyurethane particles.

[0093] Comparative Example 10: This comparative example is based on Example 3, but differs from Example 3 in that the amount of montmorillonite used in the preparation of montmorillonite-modified polyurethane is 3.5% based on the weight of the polyurethane particles.

[0094] Example 6: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; the amount of montmorillonite used is 2.0% based on the weight of polyurethane particles; and the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.5:0.2:1.

[0095] Example 7: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; the amount of montmorillonite used is 2% based on the weight of polyurethane particles; and the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.8:0.3:1.

[0096] Example 8: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; and the amount of montmorillonite is increased to 3.0% by weight of polyurethane particles; wherein the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.8:0.3:1.

[0097] Example 9: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; and the amount of montmorillonite is increased to 3.5% by weight of polyurethane particles; wherein the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.8:0.3:1.

[0098] Example 10: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; and the amount of montmorillonite is increased to 4.0% by weight of polyurethane particles; wherein the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.8:0.3:1.

[0099] Example 11: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; and the amount of montmorillonite is increased to 4.5% by weight of polyurethane particles; wherein the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.8:0.3:1.

[0100] Example 12: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; and the amount of montmorillonite is increased to 5.0% by weight of polyurethane particles; wherein the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.8:0.3:1.

[0101] Example 13: This embodiment is based on Embodiment 3, but differs from Embodiment 3 in that: carbon black and polyethyleneimine are added during the preparation of montmorillonite-modified polyurethane; and the amount of montmorillonite is increased to 5.5% by weight of polyurethane particles; wherein the mass ratio of carbon black, polyethyleneimine and montmorillonite is 0.8:0.3:1.

[0102] Comparative Example 11: This comparative example is based on Example 3, and differs from Example 3 in that: The montmorillonite-modified polyurethane was replaced with an equal amount of polyurethane particles.

[0103] Comparative Example 12: This comparative example is based on Example 3, and differs from Example 3 in that: The sealant does not contain nano-titanium salts or silane coupling agents.

[0104] Comparative Example 13: This comparative example is based on Example 3, and differs from Example 3 in that: The sealant does not contain nano-titanium.

[0105] Comparative Example 14: This comparative example is based on Example 3, and differs from Example 3 in that: The sealant does not contain silane coupling agents.

[0106] The weighted normalized impact sound pressure level (Ln,w) and impact sound pressure level improvement (ΔLw) of the sound insulation pads prepared in Examples 1 and 2 were tested respectively, as well as compressive strength, compressive deformation, and compressive creep. The compressive strength was tested according to GB / T 13480; the compressive deformation and compressive creep were tested according to GB / T 15048; the weighted normalized impact sound pressure level and impact sound pressure level improvement were tested according to GB / T 19889.8-2006 / ISO 140-8:1997 "Acoustics of buildings and building components - Measurement of sound insulation - Part 8: Laboratory measurement of impact sound improvement of heavy standard floor slab cladding". During the tests, a sample was prepared based on a pre-furnished apartment, consisting of, from bottom to top, a structural floor slab, a leveling layer, a sound insulation layer (the sound insulation system in this example, approximately 6mm thick), and a decorative layer. The results are shown in Table 2. Table 2 The data in Table 2 shows that: Whether or not nano-silica and plasticizer are added to the non-woven composite layer 1 has almost no effect on the sound insulation, energy absorption and compressive strength of the prepared sound insulation pad 100.

[0107] The weighted normalized impact sound pressure level Ln,w and the improvement in impact sound pressure level ΔLw at the seams of the sound insulation systems prepared in Examples 3-13 and Comparative Examples 7-14 were tested respectively. The results are shown in Table 3. Table 3 The data in Table 3 shows that: 1) When the sealant prepared in this embodiment is used for splicing, the sound insulation effect at the splice is comparable to that of the sound insulation pad.

[0108] 2) Compared with Example 3, the weighted normalized impact sound pressure level Ln,w of Example 4 increased and the improvement in impact sound pressure level ΔLw decreased, indicating that the sound insulation performance at the joint of Example 4 was relatively poor. The reason for this may be that the mass ratio of montmorillonite-modified polyurethane to sulfoaluminate cement in Example 4 was relatively lower. Therefore, it is speculated that the proportion of montmorillonite-modified polyurethane in cement will affect the sound insulation effect of the joint sealant.

[0109] 3) During the preparation of montmorillonite-modified polyurethane, based on the weight of polyurethane, when the amount of montmorillonite is between 1.0% and 2.5%, the sound insulation performance at the joints improves with the increase of montmorillonite content. When the amount of montmorillonite is between 2.0% and 2.5%, the improvement in impact sound pressure level ΔLw reaches the optimal level. However, when the amount of montmorillonite exceeds 2.5%, the sound insulation performance at the joints decreases with the increase of montmorillonite content.

[0110] 4) In the preparation of montmorillonite-modified polyurethane, when the amount of montmorillonite remains unchanged, the sound insulation effect at the joint can be improved slightly by adding carbon black and polyethyleneimine. The sound insulation effect is better when the amount of carbon black and polyethyleneimine is relatively large.

[0111] 5) In the preparation of montmorillonite-modified polyurethane, the sound insulation effect at the joint can be improved by adding carbon black and polyethyleneimine to appropriately increase the amount of montmorillonite-modified polyurethane. The sound insulation effect at the joint increases with the amount of montmorillonite below 4.5%, but decreases when the amount of montmorillonite exceeds 4.5%.

[0112] 6) Compared with polyurethane-based sealants, montmorillonite-modified polyurethane has significantly improved sound insulation performance, indicating that montmorillonite-modified polyurethane can enhance the sound insulation effect of polyurethane.

[0113] 7) Adding both nano-titanium and silane coupling agent to the lock sealant helps improve its sound insulation effect, and nano-titanium has a relatively greater impact on improving the sound insulation effect of the lock sealant.

[0114] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0115] It should be noted that the structures, proportions, sizes, etc., illustrated in the accompanying drawings are merely for illustrative purposes to aid those skilled in the art and to facilitate understanding and reading. They are not intended to limit the scope of the invention and therefore have no substantial technical significance. Any modifications to the structure, changes in proportions, or adjustments to size, without affecting the effectiveness and objectives of the invention, should still fall within the scope of the technical content disclosed herein. Furthermore, terms such as "upper," "lower," "left," "right," and "middle" used in this specification are merely for clarity and not intended to limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.

Claims

1. A floating floor sound insulation system, characterized in that, It is composed of several sound insulation pads (100) spliced ​​together; a locking agent is injected at the joints, the locking agent comprising the following components by weight: The composition includes 10-15 parts acrylic rubber blend emulsion, 30-40 parts nano silica, 40-60 parts sulfoaluminate cement, 5-8 parts nano titanate, 15-20 parts silane coupling agent, and 10-25 parts montmorillonite modified polyurethane; wherein the silane coupling agent is a liquid silane coupling agent; and the nano titanate is nano barium titanate. The acrylic rubber blend emulsion is prepared by mixing rubber particles with an aqueous solution made from acrylic latex powder. The montmorillonite-modified polyurethane is prepared by melt blending montmorillonite and polyurethane particles; the specific preparation process of the montmorillonite-modified polyurethane is as follows: Montmorillonite and polyurethane particles were first mixed in a high-speed mixer and then intensively mixed in a torque rheometer at a temperature of 230°C, a speed of 80 r / min, and a time of 8 min. The blend was then extruded and pulverized to obtain powdered montmorillonite-modified polyurethane. In the preparation of montmorillonite-modified polyurethane, carbon black and polyethyleneimine are added; the amount of montmorillonite used is 4.0-5.0% based on the weight of the polyurethane particles. The mass ratio of the carbon black, the polyethyleneimine, and the montmorillonite is 0.8:0.3:

1.

2. The floating floor sound insulation system according to claim 1, characterized in that, The liquid silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, 3-aminopropyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.

3. The floating floor sound insulation system according to claim 1, characterized in that, The sound insulation pad (100) consists of a non-woven composite layer (1), an elastic support layer (2), and a sound insulation and vibration damping layer (3) from bottom to top.

4. The floating floor sound insulation system according to claim 3, characterized in that, The sound insulation and vibration damping layer (3) is composed of acrylic rubber blend emulsion and butyl rubber / asphalt composite damping particles. The amount of butyl rubber / asphalt composite damping particles is 35-45% based on the weight of the acrylic rubber blend emulsion. The elastic support layer (2) is composed of acrylic rubber blend emulsion, quartz sand and halogen-free flame retardant. The amount of quartz sand is 40-50% based on the weight of the acrylic rubber blend emulsion, and the amount of halogen-free flame retardant is 20-25%.

5. A floating floor sound insulation system according to claim 4, characterized in that, The butyl rubber / asphalt composite damping particles have a particle size of 50-150 μm; the quartz sand is sieved through a 40-70 mesh screen.

6. A floating floor sound insulation system according to claim 3, characterized in that, The nonwoven composite layer (1) is formed by hot-melt penetration of crack-resistant composite material into polyester nonwoven fabric; the crack-resistant composite material includes expanded perlite and polypropylene fiber, and the mass ratio of expanded perlite to polypropylene fiber is 1:(2-4).

7. A floating floor sound insulation system according to claim 6, characterized in that, The crack-resistant composite material contains nano-silica and plasticizer. Based on the weight of the expanded perlite, the amount of nano-silica is 20-30%, and the amount of plasticizer is 8-10%.

8. A floating floor sound insulation system according to claim 3, characterized in that, The thicknesses of the nonwoven composite layer (1), the elastic support layer (2), and the sound insulation and vibration damping layer (3) are 1-2mm, 1-2mm, and 3-5mm, respectively.

9. A floating floor sound insulation system according to any one of claims 1-8, characterized in that, The seam between two adjacent sound insulation pads (100) is a T-shaped seam.

10. The method for preparing the floating floor sound insulation system according to any one of claims 5-9, characterized in that, Includes the following steps: S1. Prepare the nonwoven composite layer (1), the elastic support layer (2) and the sound insulation and vibration damping layer (3) respectively. S2. The non-woven composite layer (1), the elastic support layer (2) and the sound insulation and vibration damping layer (3) are combined to form the sound insulation pad (100), and a splicing end is formed in the sound insulation pad (100); S3. Several sound insulation pads (100) are spliced ​​together using splicing ends, and then the locking agent is injected into the splice joint at 0.3-0.5MPa.

Citation Information

Patent Citations

  • A kind of sound insulation floor with microfoam board as sound insulation cushion and its construction method

    CN104120814B

  • Sound insulation and adsorption material for indoor decoration and preparation method thereof

    CN105271943A

  • Preparation of aqueous polyurethane modified montmorillonite nanocomposite emulsion

    CN109021250A

  • Acrylic rubber sound insulation and heat preservation slurry as well as preparation method and application thereof

    CN116444224A

  • Heat preservation and sound insulation system for floating floor slab

    CN214941477U